"This Town Is Against Gender": Bending Gender in Italian Culture - Gennero, Valeria (Review of International American Studies, 2017)
Valeria Gennero University of Bergamo Italy “This Town Is Against Gender”: Bending Gender in Italian Culture This essay describes the misrepresentation of gender theory in Italian culture and politics, arguing that the violence of the attacks unleashed against gender in Italy constitutes a paradoxical example of the importance of a category of analysis that in today’s United States has come to be represented as tame (and even tedious).